Meridional Overturning Circulation Observed by the OSNAP (Overturning in the Subpolar North Atlantic Program) Array from August 2014 to May 2018 - Corrected Data - Li, Feili; Lozier, M. Susan; Bacon, S.; Bower, A.; Cunningham, S.A.; de Jong, M.F.; DeYoung, B.; Fraser, N.; Han, G.; Fried, N.; Holliday, N.P.; Holte, J.; et al. (Georgia Institute of Technology, 2021)
This item replaces a previous published version of the data with persistent identifiers: http://hdl.handle.net/1853/63707 and https://doi.org/10.35090/wa93-m688 The project scientists would appreciate it if you would use the data DOI https://doi.org/10.35090/gatech/65537 and add the following acknowledgement to any publication that use this data: “OSNAP data were collected and made freely available by the OSNAP (Overturning in the Subpolar North Atlantic Program) project and all the national programs that contribute to it (www.o-snap.org).” Strength of the Meridional Overturning Circulation across the OSNAP array, defined as the maximum of the streamfunction in density space. An international effort, Overturning in the Subpolar North Atlantic Program (OSNAP), is a partnership among oceanographers from the US, UK, Germany, the Netherlands, Canada and China whose goal is to measure and understand what drives the Atlantic Meridional Overturning Circulation (MOC) and its variability. OSNAP is consisted of more than 53 moorings that stretch from Labrador to Greenland to Scotland, providing a continuous record of the full water column, trans-basin volume transports in the subpolar North Atlantic. The first 4 years of data (August 2014 - May 2018) from the full OSNAP array has been used to produce the 30-day mean estiamtes of the MOC at OSNAP. All data are freely available from www.o-snap.org. item_description: Strength of the Meridional Overturning Circulation across the OSNAP array, defined as the maximum of the streamfunction in density space. The original version of this dataset is available at https://doi.org/10.35090/wa93-m688 National Science Foundation Award No. 1948335